PENGKAJIAN BERBAGAI REKOMENDASI PEMUPUKAN TERHADAP PERTUMBUHAN, KOMPONEN HASIL, DAN HASIL PADI SAWAH VARIETAS INPARI 1 - KARSIDI PERMADI (Agrotrop : Journal on Agriculture Science, 2011)
Assessment of Various Fertilizer Recommendation on Growth, Yield Components, and Yield of Inpari 1 Rice Variety. Integrated fertilizer application to new high yielding variety (HYV) and irrigation technology give largest contribution to rice production with supports of good practices and pest and disease control (IPM). Therefore, an assessment on wetland rice production with four fertilizer recommendation such as : package, ICM, NPK+LCC and PuPS (Site Specific Fertilizing on Rice). It was used Randomized Block Design with four replications were conducted in Tanjung Sari village, Pondok Salam subdistrict, Purwakarta district, in dry season 2009. The objectives were to obtain the best fertilizer recommendation on growth, yield components, and yield of Inpari 1 rice variety. The results showed that fertilizer recommendation of NPK+LCC significantly affected plant height, number of tiller, and number panicles per hill of Inpari 1 variety, while number of total grains per panicle, filled grain number per panicle, 1000 grain weight, and dry grain yield were not affected by fertilizer recommendation (Package, ICM, NPK+LCC, and PuPS). Fertilizer recommendation of NPK+LCC increased yield of 0.84 t/ha compared that to package recommendation.